Evidence for distinct cognitive deficits after focal cerebellar lesions. Issue 11 (15th October 2004) - Gottwald, B; Wilde, B; Mihajlovic, Z; Mehdorn, H M
Abstract : Objectives: Anatomical evidence and lesion studies, as well as functional magnetic resonance imaging (fMRI) studies, indicate that the cerebellum contributes to higher cognitive functions. Cerebellar posterior lateral regions seem to be relevant for cognition, while vermal lesions seem to be associated with changes in affect. However, the results remain controversial. Deficits of patients are sometimes still attributed to motor impairment. Methods: We present data from a detailed neuropsychological examination of 21 patients with cerebellar lesions due to tumour or haematoma, and 21 controls matched for age, sex, and years of education. Results: Patients showed deficits in executive function, and in attentional processes such as working memory and divided attention. Further analysis revealed that patients with right-sided lesions were in general more impaired than those with left-sided lesions. Conclusions: Those hypotheses that suggest that lesions of the right cerebellar hemisphere lead to verbal deficits, while those of the left lead to non-verbal deficits, have in part been confirmed. The generally greater impairment of those patients with a right-sided lesion has been interpreted as resulting from the connection of the right cerebellum to the left cerebral hemisphere, which is dominant for language functions and crucial for right hand movements. Motor impairment was correlated with less than half of the cognitive measures, with no stronger tendency for correlation with cognitive tests that require motor responses discernible. The results are discussed on the basis of an assumption that the cerebellum has a predicting and preparing function, indicating that cerebellar lesions lead to a "dysmetria of thought."